Isobaric vapor-liquid equilibrium for binary system of methyl caprate + methyl laurate at 2, 4 and 6 kPa. (January 2018) - Ding, Hui; Ke, Wenjing; Zhao, Dan; Wang, Lulu; Gao, Yujie; Liu, Shejiang
Highlights: The VLE data for binary system of methyl caprate and methyl laurate were measured. The Wilson, NRTL and UNIFAC models were used to reproduce the experimental values. The COSMO-SAC model was applied to predict the VLE of the binary system. Abstract: In this work, we measured the isobaric vapor-liquid equilibrium (VLE) data for the binary system of methyl caprate (1) + methyl laurate (2) at 2, 4 and 6 kPa with a modified Othmer still. The point consistency test of Van Ness test method was applied to check the thermodynamic consistency of all the experimental values, which guaranteed the reliability of our measurements. Afterwards, the experimental data were regressed by two activity coefficient models (Wilson, NRTL). Furthermore, we made the data prediction with the group contribution method (UNIFAC) and the COSMO-SAC model. The results of all the regressions and predictions are satisfying and reasonable, while the results provided by the NRTL model are relatively better than the other three models, with the root mean square deviations of temperature and vapor-phase mole fraction less than 0.33 K and 0.0069, respectively.